Molecular dynamics simulation on thermophysics of paraffin/EVA/graphene nanocomposites as phase change materials. (5th February 2020) - Zhang, Muxing; Wang, Changling; Luo, Ailian; Liu, Zhenghao; Zhang, Xiaosong
Highlights: Thermal conductivity enhanced by certain amount of graphene in paraffin/EVA. Excessive graphene in paraffin/EVA could lead to crystalline disorder. Thermal conduction in phase change materials was related to molecular mobility. Paraffin in EVA matrix with graphene is suitable for building wall materials. Abstract: Molecular dynamics (MD) simulations were conducted to evaluate paraffin/EVA/graphene nanocomposites as phase change materials (PCM) so as to study the thermophysical properties. Along with experimental fabricated paraffin PCMs in EVA matrix with or without graphene, five molecular models with graphene content ranging from 0 to 7.0 wt% were constructed. The results demonstrated microscopic distribution and structure of the three components, which therefore would affect corresponding thermal and mechanical properties under different temperatures. Non-equilibrium MD simulations showed that thermal conduction would be promoted with the introduction of graphene. However, complex interactions between EVA and graphene would restrain further improvement due to the disordered PCM crystal structures as graphene content reached 7.0 wt%. Equilibrium MD simulations exhibited agreement that the diffusion coefficient of molecules increased at first and decreased later with graphene content, consequently influencing the mobility of molecules and phonon transport.